Perspectives of international multi-center clinical trials on traditional Chinese herbal medicine - Wu, Shan; Wang, Chuanchi; Bai, Dong; Chen, Nanjie; Hu, Jingqing; Zhang, Junhua (Frontiers in Pharmacology, 2023)
With the introduction of various subjects, such as clinical epidemiology and evidence-based medicine, the qualities and levels of Traditional Chinese Herbal Medicine (TCHM) in China improved substantially, and the processes of internationalization of Traditional Chinese Medicine (TCM) are further accelerated. Since, a variety of drug products in China have been approved for marketing in other countries, and approximately 10 products have submitted the IND application to FDA of USA, of which various Chinese herbal preparations such as compound Danshen dripping pills, Xingling granules, and HMPL-004 have been approved to be investigated in phase III clinical trials. In general, multi-center studies of TCHM are increasing with years, but most of the studies are performed in some certain country, and the actual international multi-center clinical trials are very rare. Number of SCI literatures on multi-center clinical trials of TCHM that published in the recent decade also showed increasing tendency with years, despite the evident reduction in the past two years due to the influence of COVID-19 pandemic. Of the multi-center clinical trials of TCHM that performed by mainland China and other oversees regions, except for Taiwan, China, nearly 70% were focused on classic Chinese medicinal formulae and Chinese patent medicine, while the other 30% were on dietary supplements and plant extracts. Facing the future, the “human experience” has attracted close attentions from researchers throughout the world. Effectively utilizing the historic “human experience” is an important method to vitalize potential of original scientific and technological resources of TCHM. Performing multi-center clinical trials with high qualities is still an essential method for TCHM in accessing the mainstream medicine market. In addition, it is also required to further improve the evaluation techniques and methods that not only meet the international standards but also meet the characteristics of TCHM. Furthermore, we should also focus on the TCHM specific clinical values and scientific reports.